Multimodal Digital Learning and Local Indigenous Frameworks to Enhance Critical Thinking in History Learning - Suci Rahayu; Sariyatun Sariyatun; Leo Agung Sutimin; Deny Tri Ardianto (Ianna Journal of Interdisciplinary Studies)
Background: Critical thinking is fundamental to teaching history, yet student analysis is often limited by traditional methods that rely primarily on lecture. Using local Indigenous history in context and accessing multimodal digital materials enhances the learning experience and encourages active thinking at a higher level.